Ex vivo magnetic resonance angiography to explore placental vascular anatomy. (October 2017) - Chen, Bailiang; Duan, Jie; Chabot-Lecoanet, Anne-Claire; Lu, Huanrong; Tonnelet, Romain; Morel, Oliver; Beaumont, Marine
Abstract: Introduction: A normal placenta development is crucial for a successful pregnancy. In case of major obstetric complications such as intra-uterine growth restriction, the placental vascularization morphological alteration at macroscopic level is less known than that at microscopic scale. Ex vivo MRA has the potential to visualize whole fresh human placental vasculature fast and efficiently but can be hampered by contrast agent extravasation problem. This study aimed to provide an optimized ex vivo MRA protocol to acquire understanding of global human placenta vasculature morphology. Methods: Six fresh normal human placentas were imaged with two contrast agents (i.e. Gd-chelate and pump oil) using different imaging parameters on a 3T clinical MR scanner (GE). The contrast to noise ratio, signal to noise ratio and enhancement efficiency were assessed in order to decide which contrast agent and imaging protocol was better. In the end, morphology indices were measured based on the 3D vasculature models reconstructed from the placentas imaged with the optimized protocol. Results: With the same imaging parameters, the CNR and the enhancement efficiency of images enhanced with pump oil were superior to those using Gd-chelate. Enhanced by pump oil, an optimized ex vivo MRA protocol was determined, leading to a clear 3D visualization and reconstruction of human placenta vascularization. Discussion: The proposed ex viv o MRA method is easy to manipulate, and can be used to investigate the human placental vasculature morphology. The acquired data are of good quality and can be used for characterization of placenta vascularization morphology. Highlights: Global human placental vasculature: visualization, modelling, and characterization. Ex vivo MRA. An optimized imaging protocol at clinical MRI.